Prevalência e fatores associados à violência contra idosos no município de Uberaba – Minas Gerais - PAIVA, Mariana Mapelli de (2014)
The speed of the demographic and epidemiological transition process experienced by Brazil brought key issues for managers and researchers due to social inequality, poverty and fragile institutions. In this context highlights the development of violence affecting all social levels and causes, further deaths, physical and emotional trauma; become a challenge for the health sector. This study aimed to verify the prevalence of physical and psychological violence; only physical and psychological among the elderly in the last 12 months; characterize the sociodemographic and economic variables, health and functional capacity among elderly in violence and those without risk; compare the demographic, economic variables, housing conditions, clinical indicators and functional ability among older people at risk of violence and those without risk and those without risk and identify factors associated with physical and psychological factors by sociodemographic characteristics, health and functional capacity. Home, analytical and cross-sectional survey conducted with 729 elderly in the city of Uberaba. The instruments used were: Mini Mental State Examination, structured instrument for characterization of sociodemographic, clinical and economic indicators data, Scale of Independence in Activities of Daily Living, Lawton and Brody Scale, Conflict Tatics Scales-1. Data collection was conducted in the home of the elderly in the period January-April 2014. Data were subjected to descriptive analysis and chi-square test (p < 0,05). To analyze the predictive variables in the occurrence of violence it was used the logistic regression model using the Statistical Package for the Social Sciences (SPSS), 17.0 version. The project was approved by the Ethics Committee on Human Research of UFTM, no 573.833. The prevalence of violence was 20.9%, of which 5.9% in physical violence and 20.9% psychological. The characteristics of the elderly undergoing physical and psychological violence and physical and psychological stratified were similar whichever women, aged 60|-80 years, education, income, and with the primary aggressor spouse. Elderly subjected physical and psychological violence were living with a spouse; they had negative self-rated health, they were hospitalized last year and they had two or more comorbidities. Predictors of physical and psychological violence were between the age of 60|-80 years, living with your spouse and instrumental activities of daily living. Whereas violence is considered multifactorial, the results of this study add to the knowledge factors that are related to aggression in the elderly, as well as the main characteristics of this population victim of aggression. Thus it contributes to the strengthening of public policies addressing violence and constitutes a tool for the planning of public health.